Sistem Pergaulan Pria dan Wanita Menurut Perspektif Alquran - Rodiatam Mardiah (Jurnal Penelitian Medan Agama, 2019)
This article aims to explain how the social system between men and women in the perspective of the Koran. The Association of Men and women who gave birth to various interactions that require the arrangement is referred to as an-Nizham al-Ijtima'i. This system, in fact, governs the association between the two opposing types (men and women) and manages the various interactions arising from the association. The male and female social system of Islam suffered a devastating shock because it was far from Islamic Shari'a. An-Nizham al-Ijtima'i. Only to refer to a system that governs the association of men and the interaction that arises from the association, as well as explaining every thing that is branched from the interaction. All of them will be explained using book analysis methods and Library studies. In general, today's association is wider with the emergence of social media in life, whether it be in families, communities, and employment agencies. The association between men and women can not be separated from social media from either Facebook, Whatsup, Twitter so that parents should not neglect the supervision of the Association of men and women, especially adolescent children today, in a journal that I write will clearly explain the association that is made in Islamic law.